Pengaruh Kualitas Pelayanan Kesehatan Terhadap Kepuasan Pasien Pengguna Bpjs Di Upt Puskesmas Pematang Johar - Rahma, Sal Sabil (Green Publisher Indonesia, 2025)
This study aims to analyze the impact of healthcare service quality on the satisfaction of BPJS patients at UPT Puskesmas Pematang Johar. Using a quantitative approach with descriptive and analytical design, this study involved 86 respondents selected randomly. Data was collected through a questionnaire that measured service quality dimensions based on the SERVQUAL model, including reliability, responsiveness, assurance, empathy, and physical evidence. Linear regression analysis showed that empathy (β = 0.38), responsiveness (β = 0.32), and reliability (β = 0.28) significantly affected patient satisfaction. Meanwhile, physical evidence (β = 0.15) and assurance (β = 0.13) had a smaller, though still relevant, impact. Overall, the regression model explained 67.3% of the variation in patient satisfaction. These findings highlight the importance of improving interpersonal quality in healthcare services, especially the aspects of empathy, responsiveness, and reliability, as strategies to enhance BPJS patient satisfaction at Puskesmas. This research contributes to the development of more effective healthcare service policies and suggests improvements in interpersonal communication training and the capacity of healthcare personnel at primary healthcare facilities.